Flower orientation influences floral temperature, pollinator visits and plant fitness. Issue 2 (5th August 2021) - Creux, Nicky M.; Brown, Evan A.; Garner, Austin G.; Saeed, Sana; Scher, C. Lane; Holalu, Srinidhi V.; Yang, Daniel; Maloof, Julin N.; Blackman, Benjamin K.; Harmer, Stacey L.
Summary: Effective insect pollination requires appropriate responses to internal and external environmental cues in both the plant and the pollinator. Helianthus annuus, a highly outcrossing species, is marked for its uniform eastward orientation of mature pseudanthia, or capitula. Here we investigate how this orientation affects floral microclimate and the consequent effects on plant and pollinator interactions and reproductive fitness. We artificially manipulated sunflower capitulum orientation and temperature in both field and controlled conditions and assessed flower physiology, pollinator visits, seed traits and siring success. East‐facing capitula were found to have earlier style elongation, pollen presentation and pollinator visits compared with capitula manipulated to face west. East‐facing capitula also sired more offspring than west‐facing capitula and under some conditions produced heavier and better‐filled seeds. Local ambient temperature change on the capitulum was found to be a key factor regulating the timing of style elongation, pollen emergence and pollinator visits. These results indicate that eastward capitulum orientation helps to control daily rhythms in floral temperature, with direct consequences on the timing of style elongation and pollen emergence, pollinator visitation, and plant fitness.